Answer:
t+23=36
Step-by-step explanation:
23 is the increase increment in this situation. Then, the final temperature is 36, so you put that on the other side of the equation. Finally, you would be adding t with 23 cause of the temperature increase.
47 -14i
You can work this out in the straight-forward way, or you can recognize that (6-i) is a common factor. In the latter case, you have ...
... = (6-i)(5 + 3-i)
... = (6 -i)(8 -i)
This product of binomials is found in the usual way. Each term of one factor is multiplied by each term of the other factor and the results summed. Of course, i = √-1, so i² = -1.
... = 6·8 -6i -8i +i²
... = 48 -14i -1
... =
_____
A suitable graphing calculator will work these complex number problems easily.
One expression could be.... Nine times 4 plus five equals forty one. ALSO... Eight times eight equals sixty four then subtract twenty four equals forty one
The angle is going to be a 65° angle
Answer:
<h2>
$31,745</h2>
Step-by-step explanation:
Compound continuously:
FVn = PV x e^rn
where
PV = $20,000
r = 3.85%
n = 12 years
plugin values into the formula:
FV₁₂ = $20,000 x e ⁰°⁰³⁸⁵ ⁽¹²⁾
FV₁₂ = $31,745